Useful crises - DOBRESCU, Emilian M.; ŞTEFĂNESCU, Roxana (Annals of Spiru Haret University. Economic Series, 2010)
The autumn of 2008 has produced, starting from the American and European mortgage credits crisis, the most powerful and deep financial, monetary and economic crisis, which last phases the most advanced states of the planet seemed to be experienced in the first half of 2009. As anything that happened in the life of humans, the economic crises have not only bad, negative sides, but they also have good, positive sides.